2013
DOI: 10.1111/jofi.12045
|View full text |Cite
|
Sign up to set email alerts
|

Cheap Credit, Lending Operations, and International Politics: The Case of Global Microfinance

Abstract: The provision of subsidized credit to financial institutions is an important and frequently used policy tool of governments and central banks. To assess its effectiveness, we exploit changes in international bilateral political relationships that generate shocks to the cost of financing for microfinance institutions (MFIs). MFIs that experience politically driven reductions in total borrowing costs hire more staff and increase administrative expenses. Cheap credit leads to greater profitability for MFIs and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 47 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…Finally, some studies look at the determinants of the costs of financing. Garmais and Natividad () find that being rated strongly cuts the cost of financing, particularly for commercial lenders. Rated MFIs also lend more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, some studies look at the determinants of the costs of financing. Garmais and Natividad () find that being rated strongly cuts the cost of financing, particularly for commercial lenders. Rated MFIs also lend more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Even poor individuals with positive future income prospects or job security developed habitual profligacy as a result of easy access to inexpensive credit in the presence of a strong consumerist ethic and of ignorance regarding future consequences. In an environment of modern credit facilities and expanding loan offers, spending became constrained by liquidity rather than by income (Garmaise and Natividad 2013).…”
Section: Theorizing Global Imbalances 195mentioning
confidence: 99%
“…A handful of academic studies have examined the overall price of financing in a country, irrespective of lender differences. This work has found that MFOs pay less interest when their nation has strong market-supporting institutions (Tchuigoua, 2014) and when loans come from nations that are politically similar to their own (Garmaise & Natividad, 2013). By comparison, practitioner research has differentiated between funders, identifying two main types: commercial and public.…”
Section: Microfinance Funding and Poverty Reductionmentioning
confidence: 99%
“…In light of past research that has suggested cross-country similarities may affect microfinance funding flows (Garmaise & Natividad, 2013), we controlled for three types of lender-MFO country distance: economic (differences in economic development and macroeconomic characteristics), financial (differences in financial-sector development), and political (differences in political stability, democracy, and trade-bloc membership). Using data collected by Berry and colleagues (2010), we first calculated the average of each distance between the MFO country and all its lender countries, which generated an average score, respectively, for economic, financial, and political distance for each MFO-year.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation